2020
DOI: 10.1186/s12891-020-03328-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a nomogram to predict perioperative blood transfusion in patients undergoing total knee arthroplasty

Abstract: Background: The need for a transfusion is one of the adverse events following total knee arthroplasty (TKA), and accurately predicting this need remains challenging for arthroplasty surgeons. The purpose of the present research is to study the preoperative predictors of transfusion risk in patients following TKA and develop a nomogram. Methods: The nomogram was developed based on a training set of 5402 patients who underwent TKA at the Affiliated Hospital of Qingdao University between September 2013 and Novemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Yoshihara and Yoneoka (28) showed that middle-aged and elderly patients were more likely to receive allogeneic blood transfusions than middle-aged and young patients. Similarly, Hu et al (29) collected clinical data from more than 4,000 patients who underwent total knee arthroplasty in the Affiliated Hospital of Qingdao University and found that advanced age was an independent predictor of peri-operative blood transfusion. The older the patient's age is, the worse the hematopoietic function, and the greater the decreases in the lifespan and function of red blood cells.…”
Section: Discussionmentioning
confidence: 98%
“…Yoshihara and Yoneoka (28) showed that middle-aged and elderly patients were more likely to receive allogeneic blood transfusions than middle-aged and young patients. Similarly, Hu et al (29) collected clinical data from more than 4,000 patients who underwent total knee arthroplasty in the Affiliated Hospital of Qingdao University and found that advanced age was an independent predictor of peri-operative blood transfusion. The older the patient's age is, the worse the hematopoietic function, and the greater the decreases in the lifespan and function of red blood cells.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, it is burdensome and not always possible for patients who are scheduled for surgery to visit the hospital before surgery so that anemia can be identified and treated [ 8 ]. Furthermore, it is not possible to accurately predict which patients will develop postoperative anemia after TKA [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is burdensome and not always possible for patients who are scheduled for surgery to visit the hospital before surgery so that anemia can be identified and treated [8]. Furthermore, it is not possible to accurately predict which patients will develop postoperative anemia after TKA [9]. Intravenous (IV) ferric carboxymaltose (FCM) is an innovative IV iron formulation and stable iron complex that consists of a ferric hydroxide core stabilized by a nondextran carbohydrate shell [10].…”
Section: Introductionmentioning
confidence: 99%
“…Jo et al 7 reported Hb level, type of surgery, use of TXA, platelet count, age, and body weight as risk factors for transfusion after TKA. Hu et al 8 also presented the Hb level, age, BMI, and coronary heart disease as risk factors. However, unlike previous studies that tried to develop a prediction model including different variables, this study minimized variables to Hb level and cardiac disease by excluding TXA non-users and evaluating predictors separately depending on the surgery type.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative Hb level is a well-known and potent risk factor for transfusion after TKA 6 – 8 . Several guidelines related to patient blood management (PBM) or enhanced recovery after surgery (ERAS) have recommended correction of anemia before TKA using iron or erythropoietin supplementation 9 – 12 .…”
Section: Introductionmentioning
confidence: 99%